The Effect of Kahoot and Wordwall-Based Learning Media on Fourth-Grade Students’ Conceptual Understanding of Whole Numbers - Talsa Yulia Ananda; Siti Faizah; Riska Pristiani (Actual Insight, 2026)
Conceptual understanding is essential in elementary mathematics because it enables students to interpret numerical relationships and apply concepts in problem-solving situations. This study aimed to examine the differential effect of Kahoot and Wordwall Quiz-based learning media on fourth-grade students’ conceptual understanding of whole numbers. A quantitative approach with a quasi-experimental non-equivalent pretest–posttest design was employed. The participants were 36 fourth-grade students divided into two intact classes, with one class learning through Wordwall Quiz and the other through Kahoot. Data were collected using 15 multiple-choice items and analyzed using descriptive statistics, normalized gain (N-Gain), paired sample t-tests, and paired-samples Cohen’s d. The findings showed that both groups improved, but the improvement patterns differed. The Kahoot group showed a statistically significant increase, t(17) = 5.41, p < 0.001, d = 1.28, with an N-Gain of 0.21. Meanwhile, the Wordwall Quiz group showed a positive but non-significant increase, t(17) = 2.02, p = 0.059, d = 0.48, with an N-Gain of 0.14. The novelty of this study lies in comparing two quiz-based digital media with different interaction designs in elementary mathematics. The findings imply that digital quiz media should be integrated with conceptual explanation, reasoning discussion, and contextual problem-solving activities.